Semiotic Analysis of Moral Messages and Cultural Values in Short Film “Istiqlal” Based on Roland Barthes' Theory - Tamam, Muhammad Ibnu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
In the realm of film analysis, exploring the semiotic representations of moral messages and cultural values has become an increasingly important area of study. Short film Istiqlal is a film displayed by the moral message and cultural values until succeeded in becoming the film with the best story in the Panasonic Youth Filmmaker 2019 event because of the very mindblowing film for the film audience. This research aims to analyze the moral messages and cultural values depicted in “Istiqlal” short film using Roland Barthes' semiotic theory. The method used is a descriptive qualitative method with the aim of describing in depth the moral message and cultural values contained in the short film "Istiqlal". The results showed that there were five scenes that contained moral messages and cultural values in the istiqlal short film. The message contained is very closely related to Betawi culture. There are many moral messages that can be taken as lessons in daily life. This shows that conveying messages through film media can be one of the means to spread morals and good values that are beneficial to the audience.